Ricoeur's Kierkegaard - Helenius, Timo (International journal of philosophy and theology, 2019)
Keeping an eye on Ricoeur's philosophical anthropology in particular, this essay maps out Ricoeur's explicit references to Kierkegaard in the corpus of his major works. Even though many of these references are made only in passing, on their basis it is possible to construe a humbly withdrawing Kierkegaardian anthropology in Ricoeur's work that, I claim, is nevertheless firmly present and which will shed substantial light to Ricoeur's anthropological thought as a whole. I argue that Kierkegaard is present in Ricoeur's work in ways that so far has gone undetected in Ricoeur and Kierkegaard scholarship. This paper concludes that an extended analysis of the relation between the two thinkers is warranted, particularly regarding Ricoeur's phenomenological stance that is noticeably Kierkegaardian in some of its aspects.